Does left ventricular diastolic dysfunction progress through stages? Insights from a community heart failure study. (15th October 2016) - Banerjee, Prithwish; Motiwala, Aamir; Mustafa, Hanif Muhammad; Gani, Mohammed Akil; Fourali, Samih; Ali, Danish
Abstract: We performed a retrospective pilot study on a group of symptomatic patients attending our community heart failure clinic with left ventricular diastolic dysfunction (LVDD), rising or elevated LV end diastolic pressure, elevated brain natriuretic peptide (BNP), but with no clinical or radiographic evidence of heart failure; a group we hypothesised may be in the pre-HFPEF stage. Methods: Those with LVEF > 45% and LV diastolic dysfunction were included and divided into two groups: E/e′ < 15 and E/e′ ≥ 15 corresponding with rising and raised LVEDP, respectively. Clinical events (deaths and hospital admissions) were compared at 1 year and were grouped into all-cause events or cardiovascular events. The total numbers of all-cause and cardiovascular events of the individual groups and the entire cohort were assessed at 1 year. Results: Out of 584 screened, 80 patients were included. Thirty five patients had E/e′ < 15 and 45 had E/e′ ≥ 15. At 1 year follow-up the 1 year all-cause events in the E/e′ ≥ 15 group was higher compared to the E/e′ < 15 group (p = 0.03). At 12 months, in the entire cohort there were a total of 45 clinical events (39 hospital admissions and 6 deaths) out of which 20 events were cardiovascular. Conclusion: Patients in the pre-HFPEF stage had many events and those with elevated E/e′ ≥ 15 had a poor 1 year outcome. As this was strongly influenced by comorbidities we suggest close monitoring of these patients in dedicated HFPEF clinics along with vigorous management of comorbidities.